2011
DOI: 10.1177/0143034311424660
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of School Psychology International, 1990–2011: An analysis of trends and compatibility with the NASP Practice Model

Abstract: Formal analysis of research publications serves as one indicator of the current status of a profession or a journal. Content analyses provide both practitioners and academicians with information on the status of research in the profession. These types of analyses can also provide information on the concordance between published research and what professional organizations consider key areas of practice. The current study examined articles published in one journal, School Psychology International, for a 22-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…() and several other publications, we use the term school psychology or school psychologist to reflect all of the various titles that are used internationally (e.g., educational psychologist, psychologist in education) to describe the professionals working within this subdiscipline of psychology. Evidence also suggests that individuals assuming any one of these titles publish in and consume scholarship from the school psychology journals discussed in the present paper (e.g., Jennings et al., ; Little et al., ).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…() and several other publications, we use the term school psychology or school psychologist to reflect all of the various titles that are used internationally (e.g., educational psychologist, psychologist in education) to describe the professionals working within this subdiscipline of psychology. Evidence also suggests that individuals assuming any one of these titles publish in and consume scholarship from the school psychology journals discussed in the present paper (e.g., Jennings et al., ; Little et al., ).…”
mentioning
confidence: 71%
“…To best answer our research questions and remain consistent with similar studies (Arnett, ; O'Gorman et al., ; Pieterse et al., ), we separated the United States and Canada from “other countries in the Americas” (henceforth referred to simply as Other Americas for brevity). For example, our last research question focused on articles published outside of the United States because prior research has clearly shown that most psychology journals, including SPI, receive an overrepresentation of articles authored by individuals working in the United States (Arnett, ; Jennings et al., ; Little et al., ; O'Gorman et al., ; Pieterse et al., ), and several earlier studies have already documented characteristics related to this majority subset of experimental studies (e.g., Bliss et al., ; Burns et al., ; Villarreal et al., ). Therefore, we wanted to focus one of our research questions on the experimental research specifically conducted outside of the United States to better understand this type of research from a more international perspective.…”
Section: Methodsmentioning
confidence: 99%
“…A number of researchers have also conducted content analyses regarding areas of concern within counselor education, including problematic behavior (Brown, ), clinical preparation of school counselors (Akos & Scarborough, ), and crisis preparation (Barrio Minton & Pease‐Carter, ). A review of the literature shows that this method can be particularly useful for illuminating trends in related professions, such as teaching of psychology (Griggs & Collisson, ), school psychology (Little, Akin‐Little, & Lloyd, ), marriage and family therapy (Winston & Piercy, ), and social work (Wike, Bledsoe, Bellamy, & Grady, ). Without a systematic evaluation of literature regarding learning in counselor education, it remains difficult to assess the degree to which the practice of counselor education is consistent with accreditation standards and grounded in evidence‐based pedagogy.…”
mentioning
confidence: 99%
“…() examined the competencies in the NASP and APA models to determine the differences and overlaps, incidentally finding that legal and ethical issues were common to both models. Additionally, the Little, Akin‐Little, and Lloyd () content analysis was limited to coverage of the categories in NASP's practice model in only one of the main school psychology journals, School Psychology International , during a 22‐year period. Within this specified scope, they found that the NASP “Legal, Ethical and Professional Issues” had the highest percentage of coverage among all of the NASP practice categories, but the trend for this category was downward during the 22‐year period.…”
Section: Content Analysis Of Professional Publicationsmentioning
confidence: 99%